PRESERVING PROPERTYORWEALTH (HIFÚ AL-MÓL) FROM THEMAQÓØID SHARÔ‘AH’ S PERSPECTIVE:AN OVERVIEW - SUJIMON, M.S (Human Sustainability Procedia, 2018)
There have been a lot of discussionsand inputabouttheMaqÉsid al-SharÊ‘ah among the academiaaround the globe, whether in the form of presentationin the conference,seminar,training moduleor university class participations;I am here to share with you what I foresee on the importance of this subject in the context of Islamic finance.In this presentation, I refer to many materials be it from classical books of Islam suchasal-MuwÉfaqÉtof al-ShÉÏibÊ in Arabic–which Professor Dr. Muhammad Khalid Masudhas published in English entitled, ShÉÏibÊ’s Philosophy of Islamic Lawpublished by Research Institute 1995 -and other modern books like those of Professor Hashim Kamali, Principles of Islamic Jurisprudence, Professor Bernard Weis, The Search for God’sLaw based on the work of al-ÓmidÊ, al-IÍkÉm fÊ UsËl al-AÍkÉm of the University of Utah and others.